Enhancement of x-rays generated by a guided laser wakefield accelerator inside capillary tubes - Ju, J. (2012)
Electrons accelerated in the nonlinear regime in a laser wakefield accelerator experience transverse oscillationsinside the plasma cavity, giving rise to ultra-short pulsed X-rays, also called betatron radiation. We showthat the fluence of X-ray can be enhanced by more than one order of magnitude when the laser is guided by a10 mm long capillary tube instead of interacting with a 2 mm gas jet. X-rays with a synchrotron-like spectrumand associated critical energy ∼ 5 keV, with a peak brightness of ∼ 1 × 1021 ph/s/mm2 /mrad2 /0.1%BW,were achieved by employing 16 TW laser pulses.